The Invention of Prestige: People on the Mountain and the Politics of the National. (3rd July 2014) - Gergely, Gábor
Abstract : People on the Mountain (Szőts 1941) enjoys special standing in Hungarian film historiography: critics have hailed its use of real locations, deep humanity and sympathy for the downtrodden, and saw in it a precursor of Italian neorealism. This article argues that celebrations of the film's humanity and claims of its position apart from the ideologically inflected films of the period are misplaced, and that such critical readings are simply not justified by the historical context. Further, People on the Mountain is in fact the product of a state-controlled film industry and claims of the film's kinship with neorealism are greatly overstated. The article concludes by demonstrating that, contrary to accounts of unfavourable official reception, the film was very well received by industry bosses and state officials and links its reception to the film's use of a radical nationalist discourse which claimed for Hungarians precedence in Transylvania.